2014
DOI: 10.1002/acn3.133
|View full text |Cite
|
Sign up to set email alerts
|

Heterozygous Polg mutation causes motor dysfunction due to mtDNA deletions

Abstract: ObjectiveMutations in nuclear-encoded mitochondrial DNA (mtDNA) polymerase (POLG) are known to cause autosomal dominant chronic progressive external ophthalmoplegia (adCPEO) with accumulation of multiple mtDNA deletions in muscles. However, no animal model with a heterozygous Polg mutation representing mtDNA impairment and symptoms of CPEO has been established. To understand the pathogenic mechanism of CPEO, it is important to determine the age dependency and tissue specificity of mtDNA impairment resulting fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 40 publications
2
25
0
Order By: Relevance
“…17 The forebrain neuron-specific mutant mice did not exhibit either somatic symptoms as we expected 18 or sensorimotor dysfunction including ataxia and Parkinsonism, working memory deficits or cognitive impairment during the episodes and non-episode periods (Supplementary Figure 4a–c and Supplementary Movies 1–3). Among the psychiatric diagnoses of mitochondrial disease patients, the most common diagnosis is major depression (54%) followed by bipolar disorder (17%) and panic disorder (11%).…”
Section: Discussionmentioning
confidence: 68%
“…17 The forebrain neuron-specific mutant mice did not exhibit either somatic symptoms as we expected 18 or sensorimotor dysfunction including ataxia and Parkinsonism, working memory deficits or cognitive impairment during the episodes and non-episode periods (Supplementary Figure 4a–c and Supplementary Movies 1–3). Among the psychiatric diagnoses of mitochondrial disease patients, the most common diagnosis is major depression (54%) followed by bipolar disorder (17%) and panic disorder (11%).…”
Section: Discussionmentioning
confidence: 68%
“…Small truncated mtDNAs with large deletions (for example, 30% of the total length) can be maintained in mitochondria if the region involved in replication (mtDNA control region or the D-loop region) is intact. Replication of deleted mtDNAs can be completed in a shorter time and they may increase in abundancy preferentially (27,28). Probably by chance, human mtDNA has two identical 13-bp sequences separated by 4977 bp (Figure 1), and the approximately 5-kb DNA stretch between the two sites is likely to be lost (called "common deletion").…”
Section: The Current Understanding Of Mtdnamentioning
confidence: 99%
“…This suggests that a repair system working on mtDNA is similar to microhomology-mediated end joining, one of the nuclear DNA repair systems (29), and a mtDNA replication-dependent repair pathway (30), although mtDNA was previously thought to lack efficient DNA repair mechanisms. Our sensitive quantitative polymerase chain reaction method for assaying deleted mtDNA in mutant mtDNA polymerase (Polg) knock-in mice showed that multiple deleted mtDNAs were more abundantly accumulated in the neural tissues (28). Although neurons are in a postmitotic state, mtDNAs in the cells are actively metabolized (i.e., replicated and degraded).…”
Section: The Current Understanding Of Mtdnamentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to primary mtDNA diseases, defects of the mitochondrial replisome may lead to different, frequently coexisting, mtDNA aberrances: point mutations are often found along with mtDNA deletions in the same patient/tissue. A mouse line expressing a proofreading-deficient Pol g-a variant, the so-called mutator mouse, may serve as an important model for the understanding of this phenomenon, as the accumulation of multiple large-scale deletions in its mtDNA has been observed (Trifunovic et al, 2004;Fuke et al, 2014), in addition to the expected accumulation of point mutations (Vanderstraeten et al, 1998;Spelbrink et al, 2000). Despite a previously considered possibility that the accumulation of point mutations may predispose mtDNA molecules to deletions, no correlation has been found between the distribution of point mutations and the deletion breakpoints (Wanrooij et al, 2004;Hudson and Chinnery, 2006).…”
Section: Introductionmentioning
confidence: 99%